Emodin Scavenging of Superoxide Radical Includes π-π Interaction. X-Ray Crystal Structure, Hydrodynamic Voltammetry and Theoretical Studies - Miriam Rossi; Kelly Wen; Francesco Caruso; Stuart Belli (MDPI AG, 2020)
The naturally occurring anthraquinone emodin is found in many plants that have been part of traditional Chinese medicine (TCM) for thousands of years. Recent pharmacological studies suggest that emodin might be a valuable therapeutic option for the treatment of various diseases. We describe the antioxidant effects of emodin on the superoxide radical. Our techniques include X-ray crystallography, density functional theory (DFT), and a recently developed cyclovoltammetry improvement, the rotating ring-disk electrode (RRDE) method. X-ray results show offset π−π stacking of emodin units in the crystal, and this type of interaction is supported by the DFT, which indicates one superoxide interacting via π−π stacking with the quinone moiety, by transferring one electron to the ring, and inducing some quinone aromatization. The second superoxide seems to form a stable complex after interacting with the H(hydroxyl) in position 3 of emodin. We show that one molecule of emodin sequesters two molecules of superoxide: one forming a complex with H(hydroxyl) in position 3, and the other due to π−π oxidation of superoxide and emodin ring reduction. We conclude that emodin is a very strong antioxidant. Color variation in the voltaic cell was observed during the RRDE study. This was analyzed and explained using a mini-grid gold electrode for UV-Vis spectroscopy in the voltaic cell.